Analisis Ekspresif Lirik Lagu “untuk Perempuan yang Sedang Dalam Pelukan” Karya Payung Teduh : Pendekatan Pragmatik - Annisa Dinda Khairani Nasution (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Song lyrics are often a channel for poets to express a variety of emotions, from love and happiness to sadness and anger. Song lyrics are also an expression of feelings by poets based on their personal experiences. The song lyrics that will be studied in this study are the song "Perempuan yang Sedang dalam Peluk" by Payung Teduh which is an expression of feelings of calm and anxiety experienced and felt by Mohammad Istiqomah towards life for his family which is his responsibility as a head of the family. Through an expressive and pragmatic approach, the researcher wants to explore how feelings of love and the complexity of relationships can be reflected in this work, as well as the life experiences that underlie it as objects of study using an expressive analysis of the pragmatic approach. By using the pragmatic theory framework of speech acts, this study analyzes how word choice, sentence structure, and social context contribute to creating emotional effects on listeners. The data for this study is an analysis of illocutionary speech acts in the lyrics of the song "Perempuan yang Sedang dalam Peluk" by Payung Teduh with documentation data collection techniques,content analysis techniques. Then the data sources in this study use secondary data sources. The results of this study indicate that there are five types of illocutionary speech acts found in the lyrics of the song "Perempuan yang Sedang dalam Pelukan", consisting of two types of assertive speech acts and three types of expressive speech acts.